The digital challenges of school and teacher education in Norway : Some urgent questions and the search for answers - Rune Krumsvik (2006)
This paper highlights the digital challenges within education in Norway and explains how the digital revolution creates new possibilities, dilemmas and challenges for school and teacher education in our contemporary society. Today we find a consensus among policy-makers, researchers, teacher educators and school management that digital literacy and ICT implementation must be given high priority and needs to be explored more deeply in our contemporary educational institutions. Despite this consensus, previous ICT efforts have revealed that implementation of ICT in the Norwegian context has been more strongly anchored rhetorically, than in practice. Consequently, the paper focuses on whether we now have learned from the past and are entering a time of upheaval within technology implementation and asks what kind of possibilities, challenges and dilemmas teacher educators and teachers face in this new pedagogical terrain. The paper focuses on some urgent questions and the search for answers within this pedagogical area, based on research findings from PILOT (Krumsvik, IKT i det nye læringsrommet, 2 (ICT in the new learning-space, 2), Unipub, Universitetet i Oslo, 2004a; Krumsvik, Norsk Pedagogisk Tidsskrift (Norwegian Journal of Pedagogy), 88:467–480, 2004b; Krumsvik, Scand. J. Educ. Res., 49:27–50, 2005a; Krumsvik, J. Nord. Pedagog. Res., 25:190–207, 2005b; Krumsvik, ICT in the school. ICT-initiated school development in lower secondary school, University of Bergen, Bergen, 2006), other relevant research studies, policy documents and theoretical foundations.   Keywords Digital challenges, Digital literacy, ICT implementation, Teachers, New pedagogy
Keywords: éducation; littératie numérique; pédagogie